Analisis Faktor-Faktor yang Mempengaruhi Struktur Modal dan Harga Saham pada Perusahaan yang Tergabung dalam LQ 45 Periode Tahun 2011-2013 - nisak, ngizzah khalwiyatun; Ardiansari, Anindya (Management Analysis Journal, 2016)
ABSTRACT This research was conducted in companies incorporated in the LQ 45. By using purposive sampling method was obtained 33 samples of companies from various sectors except banking sector. The analytical method used is multiple linear analysis using SPSS 19. In this study, there are two dependent variables, namely capital structure and stock price, as well as three independent variables are sales growth, profitability, and the debt ratio. The results showed that the growth in sales and a significant negative effect on capital structure, profitability does not significantly affect the capital structure, debt ratio and significant positive effect on capital structure, sales growth was not significantly affect stock prices, profitability and significant positive effect on prices stock, debt ratio does not significantly affect stock prices, capital structure does not significantly affect the stock price.